Human papillomavirus vaccination intention and its associated factors among female medical college students in Hubei, China: A cross-sectional study - Huan Yang; Suneerat Yangyuen; Kemika Sombateyotha (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The uptake rate of human papillomavirus (HPV) vaccination in China is low, including among college students. In addition, medical students are the target population for the HPV vaccine, but they have poor uptake of the HPV vaccine. This study aimed to investigate factors related to HPV vaccination intention among female medical college students in Hubei Province. MATERIALS AND METHODS: This cross-sectional study was conducted on 988 female medical college students from six colleges in Hubei Province with a multistage sampling method. The data were collected by web-based online software. Multiple logistic regression was applied to explore the factors associated with the intention of HPV vaccination. RESULTS: The majority of students (85.5%) reported a high level of intention to receive HPV vaccine, about 82.3% have a willingness to pay (WTP) for HPV vaccine, and 51.5% reported that family members had never received the HPV vaccine. The students who had higher scores of knowledge of HPV, HPV infection prevention awareness, the protection motivation theory (PMT)-related factors including perceived severity, perceived response efficacy, perceived self-efficacy, and WTP for the HPV vaccine had higher intention to receive HPV vaccine. CONCLUSION: HPV vaccination intention was high in medical students. Also, it was influenced by knowledge of HPV, PMT-related factors, and WTP for HPV vaccine. Thus, consideration of these factors is important to design the HPV vaccination campaign that can increase the intention to receive HPV vaccine, which in turn may increase the HPV vaccination.